Pathophysiological Significance of GM3 Ganglioside Molecular Species With a Particular Attention to the Metabolic Syndrome Focusing on Toll-Like Receptor 4 Binding - Inokuchi, Jin-ichi; Kanoh, Hirotaka (Frontiers in Molecular Biosciences, 2022)
GM3 ganglioside, the first molecule in ganglioside family biosynthesis, is formed by transfer of sialic acid to lactosylceramide. Several dozen GM3 molecular species exist, based on diversity of ceramide structures. Among ceramide structures composed of sphingosine and fatty acids, there is a great diversity resulting from different combinations of chain length, hydroxylation, and unsaturation of fatty acid chains. Expression patterns of GM3 species in serum vary during pathogenesis of metabolic syndrome. Physiological activity of each species, and significance of the variability, are poorly understood. Our studies revealed that GM3 species with differing fatty acid structures act as pro- or anti-inflammatory endogenous Toll-like receptor 4 (TLR4) ligands. Very long-chain fatty acid (VLCFA) and α-hydroxyl VLCFA GM3 variants strongly enhanced TLR4 activation. In contrast, long-chain fatty acid (LCFA) and ω-9 unsaturated VLCFA GM3 variants suppressed TLR4 activation. GM3 interacted with extracellular TLR4/ myeloid differentiation factor 2 (MD-2) complex, thereby promoting dimerization/oligomerization. In obesity and metabolic syndrome, VLCFA-variant GM3 species were elevated in serum and adipose tissue, whereas LCFA-variant species were reduced, and such imbalances were correlated with disease progression. Our findings summarized in this review demonstrate that GM3 molecular species are disease-related endogenous TLR4 ligands and modulate homeostatic and pathogenic innate immune responses.